2020
DOI: 10.1080/24748668.2020.1823161
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of goal scoring opportunities in elite male ice hockey in relation to tactical and contextual variables

Abstract: We sought to examine whether goal scoring opportunities (GSO) in elite ice hockey was affected by tactical and contextual variables. An ice hockey specific notational match analysis instrument was applied to collect 4886 GSO from 192 competitive games in the top Swedish tier. Data were collected from one elite male team and its opponents during three consecutive competitive seasons. All GSO were categorised in tactical and contextual variables. In total, 13.2% (644) of all GSO (4886) resulted in a goal. Two lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Journal of Human Kinetics -volume 84/2022 http://www.johk.pl Furthermore, beyond playing position, we did not account for several game-related contextual variables. Indeed, a recent match-analysis report using 4886 offensive actions from 192 Swedish top-tier ice hockey games revealed that numbers of involved players and the specific game periods significantly affected goal-scoring opportunities (Lignell et al, 2020). However, no information is available regarding how game-related situational variables (f. ex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Journal of Human Kinetics -volume 84/2022 http://www.johk.pl Furthermore, beyond playing position, we did not account for several game-related contextual variables. Indeed, a recent match-analysis report using 4886 offensive actions from 192 Swedish top-tier ice hockey games revealed that numbers of involved players and the specific game periods significantly affected goal-scoring opportunities (Lignell et al, 2020). However, no information is available regarding how game-related situational variables (f. ex.…”
Section: Discussionmentioning
confidence: 99%
“…Despite analyses of multiple matches, our sample size is limited to one team, and thus, the observed differences in physical and physiological demands between defensemen and forwards could be partially explained by game-or-team specific situational factors ( Lignell et al, 2020 ) or strategies adopted by the coach. This also clearly affects the examination of fatigue, which was performed using indirect measurements of fatigue (changes in activity patterns) without any objective pre- and post-match assessments.…”
Section: Discussionmentioning
confidence: 99%
“…In ice hockey, shots on net are a practical proxy for scoring opportunities, and it is reasonable to conclude that the team with the most scoring opportunities has the better overall performance. However, shots on net does not weight the shots based on scoring probability and therefore counts shots taken far from the net (i.e., lower scoring probability) equally with shots taken in close (i.e., higher scoring probability) (22). Furthermore, shots taken from high scoring probability areas that miss the net are not counted.…”
Section: Discussionmentioning
confidence: 99%